Analysis of Post-Immunization Incidence of Covid-19 Vaccine in Health Personnel in Mataram City - Yul Khaidir; Sastrawan Sastrawan; Lalu Sulaiman (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to analyze the post-immunization co-occurrence or side effects of the Covid-19 vaccine on health personnel in Mataram City. This study is qualitative descriptive research. The informants in this study were 39 health personnel in the city of Mataram. The number of samples was determined using Snowball sampling, which stopped when the data were completed. The inclusion criteria included health personnel who had received the Covid-19 vaccination. Primary data were obtained from direct interviews and questionnaires using Google Forms. The results of this study indicated that not all health personnel experienced side effects after vaccination. In the 1st vaccine, 26 (56.41%) people experienced side effects, while 13 (43.59%) did not. The side effects experienced included drowsiness in 19 (37.25%) people, aches in 12 (23.53%) people, dizziness in 4 (7.84%) people, and mild fever in 7 (13.73%) people. In the 2nd vaccine, only 18 (50%) people experienced side effects. 11 (44.00%) felt drowsy, 4 (16.00%) had aches, and 5 (20.00%) had dizziness. The side effects experienced were classified as mild, so they did not require intensive and self-limited treatment.